2020
DOI: 10.1109/tkde.2019.2913379
|View full text |Cite
|
Sign up to set email alerts
|

Cross-Domain Sentiment Encoding through Stochastic Word Embedding

Abstract: Sentiment analysis is an important topic concerning identification of feelings, attitudes, emotions and opinions from text. To automate such analysis, a large amount of example text needs to be manually annotated for model training. This is laborious and expensive, but the cross-domain technique is a key solution to reducing the cost by reusing annotated reviews across domains. However, its success largely relies on the learning of a robust common representation space across domains. In the recent years, signi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
19
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
8
2

Relationship

2
8

Authors

Journals

citations
Cited by 36 publications
(19 citation statements)
references
References 29 publications
(61 reference statements)
0
19
0
Order By: Relevance
“…With the development of NLP, Sentiment Analysis has been paid more attention by researchers and many efforts have been made in word embeddings. Jiang et al [5] proposed Bag-of-words text representation method based on sentiment topic words, which is composed of deep neural network, sentiment topic words and context information, and performed well in Sentiment Analysis; Rezaeinia et al [6] proposed refined word embeddings method based on Part-of-Speech(POS) tagging technology and sentiment lexicons, which improved the performance of pre-trained word embeddings in Sentiment Analysis; Pham et al [7] proposed a joint model of multiple Convolutional Neural Networks (CNNs), which is focused on word embeddings from Word2Vec, GloVe and the one-hot character vectors, and it achieved good performance in aspect sentiment classification tasks; Zhou et al [8] constructed a text representation model containing TF-IDF and topic features based on LDA for Sentiment Analysis, which reduced the dimension of word vector space in the traditional representation model; Han et al [9] built a hybrid neural network model using convolutional neural networks and long short-term memory(LSTM) for document representation, and it incorporated user's and product's information; Devlin J. et al [10] proposed the BERT model to represent text, which can better reflect the modifying relationship between words in texts, and it had good performance in Sentiment Analysis tasks; Liu et al [11] proposed latent topic information of the text that used Neural topic model into word-level semantics representations to deal with the problem of data sparsity, and presented a new topic-word attention mechanism to explore the semantics of words from the perspective of topic word association; Li et al [12] proposed a framework that combined different levels of prior knowledge into word embeddings for Sentiment Analysis, which improved the performance of Sentiment Analysis; Xu et al [13] proposed an improved word representation method, which integrated the contribution of sentiment information into the traditional TF-IDF algorithm and generated weighted word vectors, and the method had higher F1 score; Peters M. E. et al [14] proposed a text representation model based on deep learning framework, and it constructed an English text representation model which contained grammar feature, semantics feature and sentiment feature by training a large number of sentiment text corpus; Hao et al [15] proposed a method for cross domain sentiment classification using random embeddings, which retained similar structure in embedding space and achieved well results in the task of Sentiment Analysis; Usama et al [16] merged multilevel features which are from different layers of the same network and different network architectures to improve the accuracy of Sentiment Analysis; Majumder et al [17] demonstrated the correlation between sarcasm detection and sentiment classification, and proposed a multitasking learning framework to improve the performance of two tasks; Ma et al [18] proposed Sentic...…”
Section: Related Workmentioning
confidence: 99%
“…With the development of NLP, Sentiment Analysis has been paid more attention by researchers and many efforts have been made in word embeddings. Jiang et al [5] proposed Bag-of-words text representation method based on sentiment topic words, which is composed of deep neural network, sentiment topic words and context information, and performed well in Sentiment Analysis; Rezaeinia et al [6] proposed refined word embeddings method based on Part-of-Speech(POS) tagging technology and sentiment lexicons, which improved the performance of pre-trained word embeddings in Sentiment Analysis; Pham et al [7] proposed a joint model of multiple Convolutional Neural Networks (CNNs), which is focused on word embeddings from Word2Vec, GloVe and the one-hot character vectors, and it achieved good performance in aspect sentiment classification tasks; Zhou et al [8] constructed a text representation model containing TF-IDF and topic features based on LDA for Sentiment Analysis, which reduced the dimension of word vector space in the traditional representation model; Han et al [9] built a hybrid neural network model using convolutional neural networks and long short-term memory(LSTM) for document representation, and it incorporated user's and product's information; Devlin J. et al [10] proposed the BERT model to represent text, which can better reflect the modifying relationship between words in texts, and it had good performance in Sentiment Analysis tasks; Liu et al [11] proposed latent topic information of the text that used Neural topic model into word-level semantics representations to deal with the problem of data sparsity, and presented a new topic-word attention mechanism to explore the semantics of words from the perspective of topic word association; Li et al [12] proposed a framework that combined different levels of prior knowledge into word embeddings for Sentiment Analysis, which improved the performance of Sentiment Analysis; Xu et al [13] proposed an improved word representation method, which integrated the contribution of sentiment information into the traditional TF-IDF algorithm and generated weighted word vectors, and the method had higher F1 score; Peters M. E. et al [14] proposed a text representation model based on deep learning framework, and it constructed an English text representation model which contained grammar feature, semantics feature and sentiment feature by training a large number of sentiment text corpus; Hao et al [15] proposed a method for cross domain sentiment classification using random embeddings, which retained similar structure in embedding space and achieved well results in the task of Sentiment Analysis; Usama et al [16] merged multilevel features which are from different layers of the same network and different network architectures to improve the accuracy of Sentiment Analysis; Majumder et al [17] demonstrated the correlation between sarcasm detection and sentiment classification, and proposed a multitasking learning framework to improve the performance of two tasks; Ma et al [18] proposed Sentic...…”
Section: Related Workmentioning
confidence: 99%
“…t-SNE, similar to transformers, examines the proximity of words to each other [27]. Hao et al tackle cross-domain sentiment alignment by applying stochastic word embedding [28].…”
Section: Topic Modeling As a Part Of Natural Language Processingmentioning
confidence: 99%
“…Furthermore, Yu et al [ 34 ] presented a new way to refine word embeddings for sentiment analysis using intensity scores from sentiment lexicons. Moreover, Hao et al [ 35 ] applied a novel stochastic embedding technique for cross-domain sentiment classification, preserving the similarity in the embedding space. Finally, Ali et al [ 36 ] proposed a system that retrieved transport content from social networks, representing the documents with word embedding techniques and achieving an effective approach to sentiment classification with 93% accuracy.…”
Section: Background and Related Workmentioning
confidence: 99%